Legal Certainty Regarding the Inclusion of Unrecorded Marriages on Family Cards - Lulu Salsabila Sudarmo; Fence M Wantu; Weny Almoravid Dungga (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
This study examines the legal certainty of including the status of